Amyand-type congenital inguinoscrotal hernia in a 70-year-old male: a diagnostic pitfall - Kaur, Ramandeep (International Surgery Journal, 2026)
Amyand hernia, defined as the presence of the vermiform appendix within an inguinal hernial sac, is a rare clinical entity and is most commonly described in pediatric and young adult populations. Presentation in elderly patients is exceptional and often represents a long-standing congenital indirect inguinoscrotal hernia. We report a case of a 70-year-old male presenting with a left-sided irreducible inguinoscrotal swelling, diagnosed as chronic hydrocele for long. Elective surgical exploration revealed a large, thickened hernial sac with dense adhesions, a tight internal ring, and the appendix with omentum as contents. The internal ring was partially incised to facilitate reduction, followed by Lichtenstein's open mesh hernioplasty. The appendix was non-inflamed, hence preserved. This case highlights a rare presentation of Amyand-type congenital inguinoscrotal hernia in old age and underscores the diagnostic challenges associated with long-standing hernias in elderly patients.